2006
DOI: 10.1002/ana.20950
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial of repetitive transcranial magnetic stimulation in patients with refractory epilepsy

Abstract: Objective: To study the antiepileptic effects of rTMS in patients with refractory epilepsy and malformations of cortical development in a randomized, double-blind, sham-controlled trial. Methods: Twenty-one patients with malformations of cortical development and refractory epilepsy underwent five consecutive sessions of low-frequency rTMS, either sham or active (1Hz, 1,200 pulses), focally targeting the malformations of cortical development. The number of epileptiform discharges in the electroencephalogram and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
172
1
10

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(189 citation statements)
references
References 42 publications
4
172
1
10
Order By: Relevance
“…37 Definitive reasons for these heterogeneous results are difficult to state because the studies differ in more than one aspect (Table 1). In the studies conducted by Fregni et al 35 and Theodore et al, 36 rTMS intensity was stronger than in the study conducted by Cantello et al, 37 and more stimuli were applied. Moreover, in the former studies, the epileptogenic zone was stimulated, whereas in the latter study, stimulation over the vertex was performed.…”
Section: Clinical Trialsmentioning
confidence: 80%
See 2 more Smart Citations
“…37 Definitive reasons for these heterogeneous results are difficult to state because the studies differ in more than one aspect (Table 1). In the studies conducted by Fregni et al 35 and Theodore et al, 36 rTMS intensity was stronger than in the study conducted by Cantello et al, 37 and more stimuli were applied. Moreover, in the former studies, the epileptogenic zone was stimulated, whereas in the latter study, stimulation over the vertex was performed.…”
Section: Clinical Trialsmentioning
confidence: 80%
“…For the three randomized, double-blinded and sham-controlled studies, only one resulted in a significant reduction of seizure frequency and interictal discharges, 35 whereas in another study a trend for a reduction of epileptic seizures was found, 36 and in a third study only significantly reduced epileptiform discharges were documented. 37 Definitive reasons for these heterogeneous results are difficult to state because the studies differ in more than one aspect (Table 1).…”
Section: Clinical Trialsmentioning
confidence: 92%
See 1 more Smart Citation
“…Several RCTs (5/12) evaluated VNS (whether implanted9, 14, 17, 31, 32 or transcutaneous6). Two evaluated HS (implanted34 or transcranial12), and the rest individually evaluated CS,35 TNS,11 rTMS,13 thalamic stimulation,33 and RNS 10, 16, 18. All pivotal RCTs were followed by open‐label extensions that allowed long‐term data collection 7, 8, 10, 16, 36…”
Section: The Evidence For Neuromodulationmentioning
confidence: 99%
“…Resective epilepsy surgery, in appropriately selected patients, is the accepted treatment of choice for DRE as supported by two randomized clinical trials,3, 4 multiple retrospective cohort series, and a practice parameter issued by the American Academy of Neurology recommending a surgical evaluation for any patient with uncontrolled disabling complex partial seizures 5. Similarly, a plethora of nonresective yet surgical DRE treatments have flourished recently, including various neuromodulation procedures6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18 and thermal‐based19 and radiation‐based neurosurgeries 20. A position statement by the Practice Management Committee Health Care Reform Workgroup of the American Epilepsy Society called for access and insurance coverage for all patients with epilepsy for more aggressive therapeutic strategies, including neurosurgery and implanted electronic devices, when medications fail to yield optimal seizure control 21.…”
mentioning
confidence: 99%